Optimalisasi Produksi Fikosianin pada Sianobakteria Laut BTM 11 dan Uji Aktivitas Antioksidannya - Baso Didik Hikmawan; Swastika Praharyawan; Kintoko Kintoko (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Phycocyanin (PC)-producing cyanobacteria has shown many pharmaceutical applications, the main one is the antioxidant properties. Biosynthesis of PC-producing cyanobacteria is affected by many factors like nitrogen availability and light intensity during cultivation. This study aims to analyze the optimum concentration of nitrogen and light intensity during the cultivation of PC biosynthesis of marine cyanobacteria BTM 11 and identify its antioxidant properties This study was an experimental laboratory method and the PC level was determined through the variation of sodium nitrate (NaNO3) as a source of nitrogen dissolved in media and using different light intensities. The most optimum nitrogen and light intensity values of PC were measured by its antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical capture method. Data was analyzed by one-way ANOVA and the post-hoc Duncan to see whether p<0.05. The result showed that there was a significant difference in the PC level that was cultivated with the variation of NaNO3 concentrations. The highest PC level was observed in media containing 525 mg of NaNO3 and the optimum light intensity of 4500 lux. The result of the antioxidant activity assay showed that the BTM11’s PC’s antioxidant activity had its IC50 at 91.89 μg/mL and the IC50 of ascorbic acid was 2.39 μg/mL